2020
DOI: 10.1016/j.biombioe.2020.105598
|View full text |Cite
|
Sign up to set email alerts
|

(Stop) burning for biogas. Enabling positive sustainability trade-offs with business models for biogas from rice straw

Abstract: Rice is the main agricultural crop in the Philippines and central to the country's food security. One main challenge of rice farming is the management of the straw after harvest. With limited uses, the rice straw is currently burned or in some cases incorporated with significant environmental impacts. However, it can be an important feedstock for sustainable bioenergy and support energy access in the Philippines. The research was conducted around a 1,000 m 3 biogas pilot plant in Laguna province, Philippines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Bioenergy has an important role in decarbonising the energy and transport sector. In addition to replacing fossil fuels, in off-grid contexts, bioenergy has the added potential for improving energy access using local biomass feedstock as Azasi et al [6] Garcia-Freites et al [10], Röder et al [15] and Welfle et al [19] showed in their SI articles. Garcia-Freites et al [10], Ordoñez-Frías et al [13] and Röder et al [15] also demonstrated how the use of residues can provide a valid waste management option as residues are often burned or disposed of in unmanaged manners, causing negative environmental and health impacts.…”
Section: Environmental Impactsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bioenergy has an important role in decarbonising the energy and transport sector. In addition to replacing fossil fuels, in off-grid contexts, bioenergy has the added potential for improving energy access using local biomass feedstock as Azasi et al [6] Garcia-Freites et al [10], Röder et al [15] and Welfle et al [19] showed in their SI articles. Garcia-Freites et al [10], Ordoñez-Frías et al [13] and Röder et al [15] also demonstrated how the use of residues can provide a valid waste management option as residues are often burned or disposed of in unmanaged manners, causing negative environmental and health impacts.…”
Section: Environmental Impactsmentioning
confidence: 99%
“…In addition to replacing fossil fuels, in off-grid contexts, bioenergy has the added potential for improving energy access using local biomass feedstock as Azasi et al [6] Garcia-Freites et al [10], Röder et al [15] and Welfle et al [19] showed in their SI articles. Garcia-Freites et al [10], Ordoñez-Frías et al [13] and Röder et al [15] also demonstrated how the use of residues can provide a valid waste management option as residues are often burned or disposed of in unmanaged manners, causing negative environmental and health impacts. In any of these cases, it is important to understand the environmental implications of bioenergy use to identify possible emission impacts and being able to mitigate emission risks or enable environmental benefits.…”
Section: Environmental Impactsmentioning
confidence: 99%
See 3 more Smart Citations